Mechanisms Involved in Exercise-Induced Cardioprotection: A Systematic Review - Borges, Juliana Pereira (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Investigação Cardiovascular. Rio de Janeiro, RJ, Brasil.